The Effectiveness of Cognitive Engagement Training on Reflective Thinking and Attention Control in Elementary School Students - Shameli, Mahboubeh; Jahanbakhsh, Zahra; Usefpour, Vahideh; Shahrokh Afshari, Iman (Iranian Journal of Neurodevelopmental Disorders, 2024)
Objective: This study aimed to examine the effectiveness of cognitive engagement training on reflective thinking and attention control in elementary school students.Methods and Materials: A randomized controlled trial design was employed, involving 30 elementary school students aged 10–12 years, randomly assigned to an intervention group (n = 15) and a control group (n = 15). The intervention consisted of eight 90-minute sessions focusing on metacognitive strategies, mindfulness, and problem-solving tasks. Data were collected at three time points (pre-intervention, post-intervention, and five-month follow-up) using validated tools: the Reflective Thinking Questionnaire (RTQ) and the Attention Control Scale (ACS). Statistical analyses, including repeated measures ANOVA and Bonferroni post-hoc tests, were conducted using SPSS-27.Findings: The intervention group demonstrated significant improvements in both reflective thinking and attention control compared to the control group. Reflective thinking scores in the intervention group increased from M = 32.45 (SD = 5.37) at pre-intervention to M = 48.62 (SD = 6.12) post-intervention, with sustained gains at follow-up (M = 45.73, SD = 5.89). Similarly, attention control scores improved from M = 24.76 (SD = 4.32) to M = 37.54 (SD = 5.01), with follow-up scores at M = 35.12 (SD = 4.84). ANOVA results revealed significant main effects for time and group, with strong interaction effects (p < .001). Bonferroni post-hoc tests confirmed significant differences between time points, highlighting the intervention's effectiveness.Conclusion: Cognitive engagement training significantly enhances reflective thinking and attention control in elementary school students, with sustained benefits over time. This intervention holds promise for improving essential cognitive skills and can be effectively integrated into educational practices.